Improving Performance of Finishing Pigs with Added Valine, Isoleucine, and Tryptophan: Validating a Meta-Analysis Model - H. R. Kerkaert; H. S. Cemin; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; K. D. Haydon; C. Hastad; Z. Post (Kansas Agricultural Experiment Station Research Reports, 2020)
Based on a recent meta-analysis, we hypothesized that increased dietary Val, Ile, or Trp could correct possible amino acid interactions caused by high dietary Leu in diets containing high levels of corn protein, namely dried distillers grains with solubles (DDGS). A total of 1,200 pigs (PIC TR4 × (Fast LW × PIC L02); initially 74.0 ± 1.38 lb) were used in a 103-d study. The 6 dietary treatments were corn-soybean meal- DDGS-based diets as follows: 1) low level of Lys-HCl (HSBM), 2) high Lys-HCl and moderate Ile, Val, Trp (NC; AA above NRC4 estimates), 3) moderate Lys-HCl and high Ile, Val, Trp (PC), and 4) PC with either increased L-Val (PC+Val), 5) L-Ile (PC+Ile), or 6) L-Trp (PC+Trp). Diets contained 30% DDGS until pigs reached approximately 217 lb, and then pigs were fed diets with 20% DDGS until market. Data were analyzed as a randomized complete block design using the lmer function in the lme4 package in R with pen considered as the experimental unit, body weight, and pen location as a blocking factor, and treatment as a fixed effect with 10 replicates/treatment. In the grower period, ADG was greater (P<0.05) for the pigs fed HSBM and PC+Val diets than the NC with PC, PC+Ile, and PC+Trp intermediate. Pigs fed HSBM were more (P<0.05) efficient than the NC and PC with PC+Val, PC+Ile, and PC+Trp being intermediate. In the late finisher period, ADG was greater (P<0.05) for pigs fed PC+Ile than that of the NC with HSBM, PC, PC+Val, and PC+Trp intermediate. Pigs fed PC+Val had greater (P<0.05) ADFI than the NC with HSBM, PC, PC+Ile, and PC+Trp being intermediate. However, PC+Ile pigs were more (P<0.05) efficient than PC+Val pigs with HSBM, NC, PC, and PC+Trp being intermediate. Overall, final body weight (BW), average daily gain (ADG), and hot carcass weight (HCW) were greater (P<0.05) for pigs fed HSBM, PC+Val, and PC+Ile diets than the NC with PC and PC+Trp intermediate. Pigs fed the PC+Val diet had greater (P<0.05) average daily feed intake (ADFI) than the NC with pigs fed HSBM, PC, PC+Ile, and PC+Trp intermediate. No differences were detected between treatments for overall F/G or other carcass characteristics. In conclusion, increasing Val or Ile in high Lys- HCl-DDGS-based diets improved growth performance and final BW compared with pigs fed diets containing high levels of Lys-HCl without added Val and Ile. These results demonstrate that the negative effects of high Leu concentrations in corn-DDGS-based diets can be corrected by increasing the ratios of Val and Ile to Lys.
Keywords: branch chain amino acids; isoleucine; lysine; swine tryptophan; valine